2006
DOI: 10.1590/s1806-37132006000200005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da capacidade de exercício em portadores de doença pulmonar obstrutiva crônica: comparação do teste de caminhada com carga progressiva com o teste de caminhada com acompanhamento

Abstract: Objective: To evaluate the applicability of the incremental (shuttle) walk test in patients with chronic obstructive pulmonary disease and compare the performance of those patients on the shuttle walk test to that of the same patients on the encouraged 6-minute walk test. Methods: A cross-sectional study was conducted, in which 24 patients with chronic obstructive pulmonary disease were selected. In random order, patients were, after an initial practice period, submitted to a shuttle walk test and an encourage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 24 publications
0
16
0
9
Order By: Relevance
“…In the same study, the decrease in SpO 2 was similar between tests, and the authors concluded that both the SCT and the TC6' are considered submaximal tests which evaluate the capacity of the patient to perform daily tasks 6 . Despite being a low cost test of easy application, the SCT, initially described in 1955, has not been suitably standardized until now 7 .Both the TC6'and the SCT are considered submaximal tests, since the patient is told to perform the activity at the highest velocity possible, with standard verbal encouragement 7,8 . The present study had the aim to compare the TC6' and the SCT in COPD patients, analyzing the behavior of the physiological variables, the distance completed and the dyspnea perception in both tests.…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, the decrease in SpO 2 was similar between tests, and the authors concluded that both the SCT and the TC6' are considered submaximal tests which evaluate the capacity of the patient to perform daily tasks 6 . Despite being a low cost test of easy application, the SCT, initially described in 1955, has not been suitably standardized until now 7 .Both the TC6'and the SCT are considered submaximal tests, since the patient is told to perform the activity at the highest velocity possible, with standard verbal encouragement 7,8 . The present study had the aim to compare the TC6' and the SCT in COPD patients, analyzing the behavior of the physiological variables, the distance completed and the dyspnea perception in both tests.…”
Section: Introductionmentioning
confidence: 99%
“…The incremental SWT 14 was conducted subsequent to the initial assessment. It consisted of 12 levels of consecutive walks on a flat route of 20 m round trip, in increasing speed.…”
Section: Methodsmentioning
confidence: 99%
“…The participants were told to walk until they feel they would not be able to maintain the required speed, i.e. be three meters before the cone when the beep was sounded 14 . The total distance (in meters) walked by the participant was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…O teste de caminhada com carga progressiva (TCP) foi realizado em um corredor plano de 10 m de comprimento e intensidade determinada por sinal sonoro padrão 8 . Os voluntários realizaram o TC6' e o TCP em dias e horas marcadas, com prévia instrução de como seriam realizados os testes, com roupas e calçados adequados, pelo menos uma hora após a última refeição 8 .…”
Section: Avaliação Clínica E Da Capacidade Físicaunclassified